2003
DOI: 10.1093/bmb/ldg004
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and micronutrient deficiencies

Abstract: Anaemia in pregnancy is a common and worldwide problem that deserves more attention. For many developing countries, prevalence rates of up to 75% are reported. Anaemia is frequently severe in these situations and can be expected to contribute significantly to maternal mortality and morbidity. After a discussion of definitions, screening for anaemia and prevalence, the relationship between anaemia and maternal mortality and morbidity will be reviewed. Micronutrient deficiency and especially iron deficiency is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…A lack of micronutrients before and during pregnancy may lead to adverse outcomes for both 1 The Undergraduate School of Human Life and Environmental Sciences, Ochanomizu University, Bunkyo-ku, the mother and her fetus 2) . In poor-resource countries, people tend to have plant-based monotonous diets 3) , and many women of reproductive age (WRA: 15-49 years old) do not consume enough micronutrient-rich food.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of micronutrients before and during pregnancy may lead to adverse outcomes for both 1 The Undergraduate School of Human Life and Environmental Sciences, Ochanomizu University, Bunkyo-ku, the mother and her fetus 2) . In poor-resource countries, people tend to have plant-based monotonous diets 3) , and many women of reproductive age (WRA: 15-49 years old) do not consume enough micronutrient-rich food.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological changes in pregnancy (expansion of plasma volume, increased erythropoiesis, and increased demand of the foetal unit for iron) occur throughout gestation and vary markedly between each individual 9 . Studies have also reported alterations in blood lead during pregnancy.…”
Section: African Health Sciences Vol 15 Issue 3 September 2015mentioning
confidence: 99%
“…A small amount of heam iron in the diet will improve absorption of non-haem iron and thus the diet composition is an important determinant of the amount of iron actually absorbed. Iron is stored in the reticulo-endothelial system as ferritin and haemosiderin (van den Broek et al, 2003).…”
Section: Iron Deficiencymentioning
confidence: 99%
“…But WHO recommends, for all pregnant women, if there are no high risk factors a combination tablet containing 60 mg of elemental iron and 250 μg of folate to be taken twice a day. Where this is not available, tablets such as ferrous sulphate, containing 60 mg of elemental iron, should be given twice a day together with one folic acid tablet (1 mg) (van den Broek et al, 2003). The side effects of oral iron administration (gastrointestinal side effects such as nausea, cramps and constipation) or women's dislike of the tablets owing to smell or taste have often being blamed for treatment failure, although a literature review (Suharno et al, 1993) found out that side effects accounted for only 10% of non compliance.…”
Section: Iron Supplementation (With Folic Acid)mentioning
confidence: 99%